مصطلح السرد وإشكالية التلقي المعرفي ــــ مقاربة نسقيةــــ - مالك, فوزي; رماش, عايشة (جامعة الوادي - University of Eloued, 2020)
ملخص: تسعى هذه الدراسة لإضاءة مصطلح السرد، ومحاولة الكشف عن تلك الأنساق المضمرة التي تهمش الإلمام بروح معناه – مصطلح السرد – ؟ والأهم ما مدى استيعاب المنظومات القرائية الحديثة لهذا المفهوم خاصةّ؛ وتعالقه بالتلقي المعرفي لدى الباحثين ضمن مسار نقله من المعرفة العلمية حتى المعرفة التعليمية؟ ولعل عملية التلقي المعرفي هي الإشكالية الحقيقية المسؤولة على تغييب الفهم السليم لمصطلح السرد خاصة أن تلك الأنساق التي تهيمن على خطاب الاستيعاب تعيش ضمن مسار عملية التلقي Abstractt : This study seeks to shed light on the term narrative, and try to reveal those implicit formats that marginalize its whole meaning -the term Narrative -? most importantly the uptake of the modern reading systems for this concept, and especially with its correlation with the cognitive reception for researchers within its path transmission from the scientific knowledge to the educational knowledge? And perhaps the process of the cognitive reception is the real problematic responsible for the invisibility of proper understanding for the term Narrative, especially that those formats dominate the discource of assimilation lives within the path of the receiving process.
The Term Narrative And The Problematic Of The Cognitive Reception - The Format Approach
مقال
Keywords: السرد ; علم السرد ; التلقي المعرفي ; النسق ; الاختلاف; Narrative ; Narrtology ; Cognitive reception ; Format ; Différance